P13. Correlation between DAP meter readings and skin doses for barium swallows. (September 2016) - Behardien-Peters, N.; Davidson, F.; Kotze, T.; Trauernicht, C.
Abstract : Introduction: Barium swallow examinations are done to evaluate the oesophagus of patients who are having difficulties in swallowing. The study involves the swallowing of a barium-sulphate suspension under fluoroscopic guidance. The X-ray images are usually taken in two to three different imaging positions (anterior, oblique, lateral). Method and materials: DAP readings were recorded for 34 barium swallow patients in the weight range from 50 to 90 kg. In addition, the kV for each procedure was recorded. The PCXMC V2.0 Monte Carlo code was used to determine the skin dose for each patient individually, taking into account the patient weight, Focus to Skin Distance (FSD) and imaging kV, as if all the dose had been deposited in the anterior position only. The field size used was 15 cm × 25 cm, but corrected for the individual FSDs. 100, 000 photon histories were done for each patient. Results: A linear fit with an R 2 = 0.973 was obtained for the DAP readings vs. the skin dose. A power equation fit with an R 2 = 0.986 improved the fit for low DAP readings. Conclusion: Bearing in mind that the Monte Carlo simulation does not take the spread of the dose over the skin for all imaging positions into account, this data still suggests a single conversion factor from DAP reading to skin dose will give a reasonable indication of an upper skin dose limit.